2022
DOI: 10.3390/ijerph192013018
|View full text |Cite
|
Sign up to set email alerts
|

Sexual History Documentation and Screening in Adolescent Females with Suicidal Ideation in the Emergency Department

Abstract: Adolescents with mental illness often seek care in the emergency department (ED) and are more likely to engage in risky behaviors such as substance abuse and unprotected sex, increasing their risk of sexually transmitted infections (STI), unintended pregnancy, and non-consensual sex. This was a retrospective study of 312 females, aged 13–17 years, presenting to the pediatric ED with the chief complaint of suicidal ideation from February to May 2018. Electronic medical records were reviewed for demographics, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Authors found provider screening rates were not associated with gender, age, race, ethnicity, or type of insurance; and this differs from the associated factor findings of Goyal et al (2014). Vayngortin et al (2022) further validate the importance of focusing on ways to enhance provider adherence with screening for sexual activity in healthcare facilities.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Authors found provider screening rates were not associated with gender, age, race, ethnicity, or type of insurance; and this differs from the associated factor findings of Goyal et al (2014). Vayngortin et al (2022) further validate the importance of focusing on ways to enhance provider adherence with screening for sexual activity in healthcare facilities.…”
Section: Introductionmentioning
confidence: 91%
“…Sexual activity screening has also been investigated among adolescent females with mental health concerns in the emergency room. Vayngortin et al (2022) retrospectively examined sexual history and risk in adolescent females presenting to the emergency department with suicidal ideation. Out of 312 females, aged 13 to 17, only 144 had a documented sexual history.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although some patients may present to the emergency department with an obvious indication for emergency contraception or may request emergency contraception, populations with a higher risk of unprotected intercourse and unintended pregnancy may not routinely be asked. In a recent chart review of a cohort of 13–17 years presenting to the pediatric emergency department with the chief complaint of suicidal ideation, Vayngortin et al [25 ▪ ] reported fewer than half (46.2%) had a documented sexual history but 34.7% reported being sexually active. Of the sexually active patients, only 56% had documentation of contraception use.…”
Section: Contraceptionmentioning
confidence: 99%
“…The roles of ideation factors in predicting behavior change were examined for cancer care [ 13 ], contraceptive use [ 14 ], suicide [ 15 ], and malaria care [ 16 ], but rarely for breastfeeding in Nigeria [ 11 ]. Examining the predicting role of maternal ideation in EBF practices can help direct and strengthen the cooperation between multidisciplinary healthcare providers in formulating multidisciplinary breastfeeding enhancement strategies.…”
Section: Introductionmentioning
confidence: 99%